EFEKTIVITAS PENGGUNAAN MODUL KOMI UNTUK KADER POSYANDU DALAM DETEKSI DINI KOMPLIKASI PADA IBU HAMIL DI KOTA TANJUNGPINANG - Asmarita Jasda; Elsa Gusrianti; Annisa Oktari Erfi (PT Nuansa Fajar Cemerlang, 2026)
Introductions : Maternal mortality in Indonesia remains high, primarily driven by complications such as preeclampsia, hemorrhage, and infection. Delays in recognizing clinical danger signs often occur at the community level, necessitating the active involvement of Posyandu (integrated health post) volunteers in early detection through routine monitoring of pregnant women. However, limited knowledge and technical skills among these volunteers in identifying such signs remain a significant obstacle. The KOMI (Maternal Complications) Module was developed as a systematic, practice-based educational tool providing comprehensive information on pregnancy danger signs to enhance volunteers' ability to perform early detection accurately and promptly. Methods : This research employed a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 60 Posyandu volunteers in Tanjungpinang City, divided into intervention and control groups. The intervention group received intensive training using the KOMI module, while the control group did not. Data were collected using structured questionnaires to measure knowledge and early detection capabilities before and after the intervention. Statistical analysis was performed using paired t-tests and independent t-tests. Results : The findings demonstrate that utilizing the KOMI module significantly improved both the knowledge and detection skills of volunteers. A statistically significant increase was observed within the intervention group following the implementation (p < 0.006). Furthermore, the average posttest scores of the intervention group were significantly higher than those of the control group. Discussion : Structured and practical module-based educational interventions serve as effective strategies for strengthening community-level health capacity. Improved early detection allows volunteers to mitigate delays in recognizing danger signs a critical factor in maternal mortality. As the frontline of community maternal monitoring, empowering volunteers is essential for better health outcomes.